On the hybrid using of unicast-broadcast in wireless sensor networks. (October 2018) - Liu, Qing; Liu, Anfeng
Highlights: A hybrid Unicast joint Broadcast Aggregation (UBA) schedule scheme is proposed in this paper. UBA scheme adopts broadcast strategy in the far sink region and unicast strategy in the near sink region. UBA scheme is proved to improve sensing information by 25% under same lifetime of network. UBA scheme is proved to reduce delay by 14% to 18% under same lifetime of network. UBA scheme is simple operation and wide applicability. Abstract: A hybrid Unicast joint Broadcast Aggregation (UBA) schedule scheme is proposed for maximizing aggregation information and minimizing delay for wireless sensor networks (WSNs). UBA scheme adopts following regimes for maximizing aggregation information and minimizing delay. (a) The nodes in the far to sink region adopt broadcast manner, which can not only efficiently collect more sensing information within the same time slot but also reduce overall network delay. (b) The nodes in the near to sink region use unicast manner to collect sensing information, which can efficiently save energy consumption to extend network lifetime. This is UBA scheme with a great advantage that it can collect more sensing information and reduce delay without shortening network lifetime. Simulation and theoretical analytical results clearly indicate that the proposed scheme can significantly improve sensing information by 25% and reduce delay by 14% to 18% under the same network lifetime. Graphical abstract: Image, graphical abstract